Shariah, Social Responsibilities and Corporate Governance of the Islamic Banks in Malaysia / Dr Halil Paino … [et al.] - Paino, Halil (Research Management Institute (RMI), 2012)
The banking and other financial institutions play a key role in the economy of Malaysia. They provide a platform to facilitate the intermediation process in the financial system. The Islamic financial services such as Islamic banks operate under a different structure of corporate governance that one used in the conventional banking. An Islamic bank is obliged to appoint a board of Islamic scholars called Shariah Supervisory Board or Shariah Advisory Council/Board (SAC). Corporate Governance in financial institutions has been analysed almost exclusively in the content of conventional commerce industry. By contrast, very little is written on governance structures in Islamic banking and other Islamic financial institutions, despite the rapid growth of Islamic banks since 1970s and their increasing presence on world financial markets (Nasser M Sulaiman, 2000). Quoting the definition by Dr Zeti Akhtar Aziz (2002), "corporate governance involves the manner in which the business and the affairs of the individual banking institutions are being governed by their board of directors and senior management, how the economic returns are generated to the owners, the day-to-day running of the operations of the business and the consideration of the interests of recognised stakeholders including depositors; and how they behave in a safe and sound manner, in compliance with applicable laws and regulations". Islamic banking in modern world aims to promote and develop the application of Islamic principles, law and traditions to transactions of financial, banking and related business affairs. It is also promote investment companies to engage in such business activities that are acceptable and consistent with the Shariah concept. The main principles of Islamic banking are the prohibitions of interest (usury) in all transactions, the undertaking business and trade activities must be on the basis of fair and legitimate profit and the prohibitions of monopoly and hoarding. By doing so, Islamic banks will safeguard the Islamic communities and societies from activities that are forbidden in Islam. In Malaysia, with Bank Negara Malaysia (BNM) regulated as a central bank, currently there are 17 local banks registered as Islamic bank, 4 international Islamic banks and another 6 banks participated in Islamic banking scheme. There are various of products range such as general account, deposits, investment account, fund based, fee based, trade finance and card services.